The spectrum of sleep-disordered breathing symptoms and respiratory events in infants with cleft lip and/or palate. Issue 12 (6th October 2012) - MacLean, Joanna E; Fitzsimons, David; Fitzgerald, Dominic A; Waters, Karen A
Abstract : Objective: To determine the prevalence of sleep-disordered breathing (SDB) symptoms and respiratory events during sleep in infants with cleft lip and/or palate (CL/P). Design: Prospective observational study. Setting: Cleft palate clinic, tertiary care paediatric hospital, before palate surgery. Patients: Consecutive newborn infants with CL/P. Main outcome measures: Demographics, clinical history, sleep symptoms, facial measurement and polysomnography (PSG; sleep study) data. Results: Fifty infants completed PSG at 2.7±2.3 months; 56% were male, and 30% had a clinical diagnosis of Pierre Robin sequence (PRS) or a syndrome. The majority of infants (75%) were reported to snore frequently or constantly, while 74% were reported to have heavy or loud breathing during sleep. The frequency of parent-reported difficulty with breathing during sleep was 10% for infants with isolated CL/P, 33% for those with syndrome, and 43% for PRS (χ 2 16.1, p<0.05). All infants had an Obstructive–Mixed Apnoea–Hypopnoea Index (OMAHI) >1 event/h, and 75% had an OMAHI >3 events/h. Infants with PRS had higher OMAHI (34.3±5.1) than infants with isolated CL/P (7.6±1.2) or infants with syndromes (15.6±5.7, F stat, p<0.001). Multivariate analysis showed that PRS was associated with higher OMAHI (B 0.53±0.22, p=0.022), but the majority of the variance for SDB was unexplained (constant B 1.31±0.55, p=0.024). Conclusions: The results highlight that infants across the spectrum of CL/P have a high risk of SDB symptoms and obstructive respiratory events before palate surgery. Clinicians should enquire about symptoms of SDB and consider investigation with polysomnography in all infants with CL/P.